A water quality control device for improving water quality and a method thereof - Matori, Mohd Fuad; Ishak, Noorazira; Mohd. Riduan, Arifah; Mohd Nor, Rosmaniar; Ali, Saipuzaman; Md Shairi, Ismail; Nordin, Fauziah; Mior Mohd Shop, Mior Mohd Nizam; Norsidin, Jefri; Sulaiman, Noraziman; Shukri, Shafik Harafi (2011)
The present invention relates to a water quality control device for improving water quality in water tank, characterized by a perforated casing comprising a perforated housing and a perforated detachable end cap covered each end of the perforated housing for allowing water passage through the perforated casing; a plurality of sachets is contained in the perforated casing; a plurality of water treatment agents is contained inside the plurality of sachets to improve water quality. A method for improving water quality in water tank by using a perforated casing to allow the water passage through the perforated casing, characterized in that the perforated casing contains a plurality of sachets in which a plurality of water treatment agents is contained inside thereof, wherein the plurality of water treatment agents comprises activated carbon, zeolites, calcium carbonate each in a dosage range of 0.3 to 0.8 g/L, and sodium thiosulphate in a dosage range of 0.03 to 0.08 g/L.